Effect of Oral Protein Supplementation on Nutritional Status and Quality of Life in Hemodialysis Patients (Bangladesh Renal Journal, 2026)
Background: Malnutrition and protein-energy wasting (PEW) are significant predictors of morbidity and mortality in patients undergoing maintenance hemodialysis (HD). This study evaluated the impact of oral nutritional supplementation (ONS) on nutritional status and health related quality of life (HRQoL) in a realworld clinical setting.Methods: A prospective quasi-experimental pre–post study was conducted at Dhaka Medical College Hospital involving 50 adult HD patients. Participants received a high-protein ONS (Fresubin HP, 42g protein/day) for one month. Nutritional status was assessed via serum albumin levels, while HRQoL was measured using a 25 item questionnaire adapted from the KDQOL-36. Statistical analysis was performed using SPSS version 26.0, employing the Wilcoxon signed-rank test to compare pre- and post-intervention biochemical markers.Results: The mean age of participants was 47.62±12.40 years. Following the one-month intervention, mean serum albumin levels increased significantly from 4.16±0.40 g/dL to 4.36±0.38 g/dL (p < 0.001). Post-intervention HRQoL assessment revealed a mean total score of 95.98±12.19 (range: 25–125). Patients reported the highest satisfaction in the “Dialysis Care” (22.06±3.35) and “Symptoms & Problems” (20.98±3.24) domains, while “Social Functioning” (16.68±2.85) and “Emotional Well-being” (17.66±3.00) remained the lowest-scoring areas.Conclusion: Short-term oral protein supplementation effectively improves serum albumin levels in maintenance hemodialysis patients, addressing critical nutritional deficits. While ONS contributes to high satisfaction regarding physical symptoms and clinical care, the persistence of lower social and emotional QoL scores suggests that nutritional interventions should be integrated into a broader multidisciplinary support framework. These findings support the routine use of high protein ONS in resource-limited renal care settings to improve clinical outcomes.Bang. Renal J. 2026; 8(2): 56-61